Relationship between Risk Management and Investment Strategy on Profit Forex Trading Online Gold - Ahyati; Dian Masita Dewi (HM Publisher, 2022)
This study aims to analyze the effect of risk management and investment strategy on online forex trading, as well as the effect of risk management, investment strategy, and online forex trading on profit trading. The type of research used is an explanatory survey. The unit of analysis is members of the trader community in Banjarbaru, South Kalimantan, totaling 178 people with the sampling technique used is purposive sampling totaling 100 respondents. The variables used are risk management (X1), investment strategy (X2), online forex trading (Z), and profit trading (Y) using the path analysis method. The results of the study state that risk management has a significant effect on online forex trading, risk management has a significant effect on profit trading, investment strategies have a significant effect on online forex trading, investment strategies have a significant effect on profit trading, and online forex trading has a significant effect on profit trading.